2013
DOI: 10.1037/a0031975
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel meta-analysis of the relationship between creativity and schizotypy.

Abstract: The purpose of this study is to obtain a more coherent picture of the relationship between creativity and schizotypy. A multilevel approach was used to ensure the statistical independence of multiple effect sizes from a single study. The mean effect size was r = .07 {SD = .20) based on the analyses from 45 articles yielding 268 effect sizes. The analyses, including five moderators (i.e., the type of schizotypy, measure of schizotypy, measure of creativity, content of creativity test, and index of creativity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
109
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 165 publications
(155 reference statements)
17
109
3
2
Order By: Relevance
“…The threshold hypothesis states that intelligence is positively related to creative thinking for low IQ levels but the relationship blurs for high IQ levels. Similar arguments arise in recent accounts of the “mad genius hypothesis”: moderate levels of inhibitory or top-down control dysfunction, characteristic of subclinical psychiatric populations (e.g., mild ADHD and schizophrenia disorders), can spur creativity under some conditions whereas clinical-severe levels typically lead to impoverished creative thinking (Schuldberg, 2005; Abraham et al, 2007; Jaracz et al, 2012; Acar and Sen, 2013; Abraham, 2014). …”
Section: Introductionsupporting
confidence: 57%
“…The threshold hypothesis states that intelligence is positively related to creative thinking for low IQ levels but the relationship blurs for high IQ levels. Similar arguments arise in recent accounts of the “mad genius hypothesis”: moderate levels of inhibitory or top-down control dysfunction, characteristic of subclinical psychiatric populations (e.g., mild ADHD and schizophrenia disorders), can spur creativity under some conditions whereas clinical-severe levels typically lead to impoverished creative thinking (Schuldberg, 2005; Abraham et al, 2007; Jaracz et al, 2012; Acar and Sen, 2013; Abraham, 2014). …”
Section: Introductionsupporting
confidence: 57%
“…Specifically, both madness (i.e., psychosis) and genius (i.e., high creativity) have been linked to a hyperactive RH, where facilitated formation of abnormal associations could stimulate both delusional and creative ideas (Bracha 1989;Leonhard and Brugger 1998;Pizzagalli et al 2001;Taylor et al 2002;Krummenacher et al 2010). This notion is supported by studies showing that individuals expressing positive schizotypical traits, that is, schizophrenia-like thought patterns and perceptions including odd beliefs, paranormal thoughts, and unusual perceptual experiences, display increased associative processing Mohr et al 2001Mohr et al , 2006, specifically in the RH, as assessed through a lateral semantic priming task , and increased creativity (Leonhard and Brugger 1998;Weinstein and Graves 2002;Folley and Park 2005;Nettle and Clegg 2006;Acar and Sen 2013). Moreover, recent meta-analyses revealed a relationship between creativity, approach motivation (Baas et al 2008) and vulnerability to approach-based psychopathologies (i.e., positive schizotypy and bipolar disorder; Acar and Sen 2013;Baas et al 2016), and negative correlations between creativity, avoidance motivation and inclinations towards avoidance-based psychopathologies (i.e., negative schizotypy, anxiety, and depression Acar and Sen 2013;Baas et al 2016).…”
Section: Hemispheric Reward Asymmetry and Hemispheric Asymmetries Inmentioning
confidence: 54%
“…This notion is supported by studies showing that individuals expressing positive schizotypical traits, that is, schizophrenia-like thought patterns and perceptions including odd beliefs, paranormal thoughts, and unusual perceptual experiences, display increased associative processing Mohr et al 2001Mohr et al , 2006, specifically in the RH, as assessed through a lateral semantic priming task , and increased creativity (Leonhard and Brugger 1998;Weinstein and Graves 2002;Folley and Park 2005;Nettle and Clegg 2006;Acar and Sen 2013). Moreover, recent meta-analyses revealed a relationship between creativity, approach motivation (Baas et al 2008) and vulnerability to approach-based psychopathologies (i.e., positive schizotypy and bipolar disorder; Acar and Sen 2013;Baas et al 2016), and negative correlations between creativity, avoidance motivation and inclinations towards avoidance-based psychopathologies (i.e., negative schizotypy, anxiety, and depression Acar and Sen 2013;Baas et al 2016). Strikingly, we recently showed that increased expressions of approach (vs. avoidance) behaviours were associated with relatively decreased ventral striatal reward responses in the RH (Aberg et al 2015, see also Maril et al 2013Porat et al 2014;Tomer et al 2014).…”
Section: Hemispheric Reward Asymmetry and Hemispheric Asymmetries Inmentioning
confidence: 54%
“…These dimensions of schizotypy have different implications for cognitive functioning, well-being and creativity (Holt, 2015). In particular, negative schizotypy has been associated with lower-levels of well-being, poor executive functioning and lower levels of creativity (Abbott, Do & Byrne, 2012;Acar & Sen, 2013;Dinn et al, 2002); while positive schizotypy has been inconsistently associated with well-being and executive functioning, and correlates positively with creativity (Abbott, Do & Byrne, 2012;Acar & Sen, 2013;Dinn et al, 2002;Mohr & Claridge;2015;Tabak & Weisman de Mamani, 2013).…”
Section: Introductionmentioning
confidence: 99%